Anxiety Level in students Interpersonal Communication with Academic Supervisors - Muhammad Fauzan; Asmidir Ilyas; Zadrian Ardi (Universitas Negeri Padang, 2020)
Anxiety is a state of fear or an unpleasant feeling caused by many things such as individual health, social relations and so forth. Interpersonal communication anxiety is a from of anxiety experienced by individuals when they have to talk to others. The purpose this study is to describe the level of student anxiety in interpersonal communication with academic supervisors viewed from physical symptoms, mental or cognitive symptoms and emotional symptoms. The type of research used is descriptive research. The research population of the students of the Guidance and Counseling, Faculty of Education, Padang State University in 2019 the were 214 students. Samples were taken using simple random sampling technique, so that a total sample of 139 students was obtained. The study was conducted by administering the questionnaire instrumen. Data were analyzed by percentage analysis. The study shows the results (1) anxiety level in students interpersonal communication with academic supervisors as a whole is in the medium category, (2) anxiety level in students interpersonal communication with academic supervisors seen from physical symptoms in the medium category, (3) anxiety level in students interpersonal communication with academic supervisors seen from mental or cognitive symptomsin the medium category, (4) anxiety level in students interpersonal communication with academic supervisors seen from emotional symptoms in the medium category.